2018
DOI: 10.3390/infrastructures3040043
|View full text |Cite
|
Sign up to set email alerts
|

Smart Libraries

Abstract: Can the smart city provide a new perspective for public and academic libraries? How does the smart city impact the libraries as cultural and scientific assets? And how can libraries contribute to the development of the smart city? An overview of recent library models, like the learning center or the green library, reveals affinities with the concept of the smart city, especially regarding the central role of information and the integration of technology, people, and institutions. From this observation, the pap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 25 publications
3
32
0
3
Order By: Relevance
“…Such solutions can spontaneously self-assemble constituent pieces of data into a knowledge package with a particular property and then bring it to the individual with the relevant interest. Schöpfel (2018) stated that the smart library concept can be understood as an approach that introduces consistency into several recent 'modern' library developments in the urban environment. Mohapatra et al (2017) observed that due to the use of smart technologies in modern library systems, they are able to provide smart services to users, thus becoming smart libraries.…”
Section: Literature Review the Concept Of Smart Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…Such solutions can spontaneously self-assemble constituent pieces of data into a knowledge package with a particular property and then bring it to the individual with the relevant interest. Schöpfel (2018) stated that the smart library concept can be understood as an approach that introduces consistency into several recent 'modern' library developments in the urban environment. Mohapatra et al (2017) observed that due to the use of smart technologies in modern library systems, they are able to provide smart services to users, thus becoming smart libraries.…”
Section: Literature Review the Concept Of Smart Librarymentioning
confidence: 99%
“…To summarise, the fundamental factors and key conceptual components of the smart library can be classified into three categories: smart technology (IoT, data mining and AI), smart service (user-centred service) and smart people (user and librarian). Schöpfel (2018) has pointed out that the smart library can be described in four dimensions: smart services, smart people, smart place and smart governance.…”
Section: Review Successful Cases Regarding the Smart Librarymentioning
confidence: 99%
“…Next, Schopfel (2018) said that: Can the smart city provide a new perspective for public and academic libraries? How does the smart city impact the libraries as cultural and scientific assets?…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ezt az okoskönyvtár modelljének tekinti. 6 Ez az új könyvtártípus a felhasználók és a dokumentumok közötti interakcióra épül, tehát emberközpontú. A megvalósítását elősegíteni hivatott eszköz, a tárgyak internete felhőalapú számítástechnikára (cloud computing) és intelligens eszközökre (smart devices) támaszkodik.…”
Section: Az Okoskönyvtár (Szakirodalmi Kitekintés)unclassified